2019
DOI: 10.1111/nep.13620
|View full text |Cite
|
Sign up to set email alerts
|

Association between exercise training in haemodialysis patients and burden of their family caregivers: A cross‐sectional study

Abstract: Aim Considering that exercise programmes are related with a range of benefits for end‐stage renal disease patients, we evaluated the association between haemodialysis (HD) patients’ involvement in intradialytic exercise training with the burden of their family caregivers. Methods In this cross‐sectional study, 60 caregivers of HD patients were recruited, 30 of them who cared for patients that regularly participated in an exercise programme during dialysis sessions and 30 caregivers who looked after patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Limited studies focus on the caregivers doing exercise to relieve CB. One study focused on the effectiveness of the involvement of care recipients in intradialytic exercise and found that it successfully reduced CB [77].…”
Section: Consistency Between Studiesmentioning
confidence: 99%
“…Limited studies focus on the caregivers doing exercise to relieve CB. One study focused on the effectiveness of the involvement of care recipients in intradialytic exercise and found that it successfully reduced CB [77].…”
Section: Consistency Between Studiesmentioning
confidence: 99%
“…Many of our interviewed care partners suggested that such a program may improve their quality of life whether indirectly (through improved patient functioning) 78 or through joint participation. However, it should be acknowledged that the barriers care partners reported motivating their patients to exercise (eg, health problems, competing priorities for time) could potentially apply to joint participation as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, surprisingly few studies have addressed the importance of caregivers to the success of exercise interventions in elderly populations. At least one study suggests that exercise training for dialysis patients may improve QoL for the caregivers of such patients [51]. To our knowledge, no study has elicited caregiver input on the burden of such interventions on the caregiver or how the caregiver could assist the patient to successfully participate.…”
Section: Discussion/conclusionmentioning
confidence: 99%